Can persuasive and demonstrative messages to visitors reduce littering in river beaches? - Cingolani, Ana María (2016)
Littering of public areas is a significant problem worldwide. Here we evaluate the success of persuasive and demonstrative messages at reducing littering in highly visited river beaches in Argentina. We made an intervention at the beaches which consisted of a personalized verbal request asking visitors to taketheir litter to the waste cans (persuasive message) while they were exposed to the example of picking up the litter already left on the beach (demonstrative message). We conducted 102 observations distributed over 29 dates, two years and four beaches. Each observation consisted of three or four rounds: before the presence of visitors we cleaned the beaches, during the stay of visitors we made the intervention (once or twice) in two out of the four beaches, and early next morning we estimated the amount of litter left per beach. Litter weight ranged from 0 to 53 g visitor1 day1. Littering per visitor was reduced an average of 35% due to the intervention (p = 0.049). We also found differences among beaches(p = 0.001), and an increase in littering with crowding (p = 0.005). We show for the first time that the personalized request combined with the example of picking up litter is effective in reducing littering in a Latin American country.